2013
DOI: 10.1523/jneurosci.3289-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Auditory–Motor Interactions for the Production of Native and Non-Native Speech

Abstract: During speech production, auditory processing of self-generated speech is used to adjust subsequent articulations. The current study investigated how the proposed auditory-motor interactions are manifest at the neural level in native and non-native speakers of English who were overtly naming pictures of objects and reading their written names. Data were acquired with functional magnetic resonance imaging and analyzed with dynamic causal modeling. We found that (1) higher activity in articulatory regions caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Thus, learning relies on the transmission of these signals to frontal regions involved in motor planning and execution. In keeping with this view, Parker Jones et al (2013) noted stronger functional connectivity between motor and auditory areas in nonnative speakers than native speakers during an overt production task. The correlation we found between learning success and white matter FA underlying pSTs (Figure 4, middle ) supports this interpretation.…”
Section: Discussionsupporting
confidence: 54%
“…Thus, learning relies on the transmission of these signals to frontal regions involved in motor planning and execution. In keeping with this view, Parker Jones et al (2013) noted stronger functional connectivity between motor and auditory areas in nonnative speakers than native speakers during an overt production task. The correlation we found between learning success and white matter FA underlying pSTs (Figure 4, middle ) supports this interpretation.…”
Section: Discussionsupporting
confidence: 54%
“…Although we showed that loud speech production did not help reduce the responses to DAF in the ASD group, it could not be ruled out that these two groups of participants utilized air- and bone-conducted auditory feedback in a different way. In addition, future studies should investigate which parts of the brain areas responsible for speech production ( Hashimoto and Sakai, 2003 ; Takaso et al, 2010 ; Hickok et al, 2011 ) are affected in ASD and verify our finding that speech production in individuals with ASD relies more on feedback control than on feedforward control on a neural basis ( Parker Jones et al, 2011 ).…”
Section: Discussionmentioning
confidence: 53%
“…We find that while school-age children and young adults do show many commonalities in activation (and condition-specific modulations of activation), there are large and regionally specific developmental differences in activation for picture naming that would not be picked up using one task alone, or one baseline alone. Not only do children and adults show quite different patterns of auditory-related activation potentially associated with speech monitoring ( Dhanjal et al 2008 ; Simmonds et al 2011 ; Agnew et al 2013 ; Parker Jones et al 2013 ), and differences in higher-order visual areas ( Cohen Kadosh et al 2013 ), we find that they show fundamentally different responses in frontal regions to incremental increases in naming difficulty.…”
Section: Introductionmentioning
confidence: 63%
“…In a study analogous to the present one, Parker Jones et al (2012 , 2013 ) compared monolingual English speakers and bilingual nonnative English speakers on a series of fMRI tasks requiring overt speech production—picture naming, reading, saying 1–2–3 to unfamiliar nonobjects and saying 1–2–3 to meaningless letter strings (in triads). Under a skill-learning account, we might expect that activation comparisons of nonnative to native speakers should pattern in the same way as the present study's comparison of children versus adults.…”
Section: Discussionmentioning
confidence: 98%